The Effect of Brand Loyalty. Brand Awareness, Brand Image Against Brand Equity on Indomie Products - Kabangunan, Rizaldy; Hidayat, Anas (Archives of Business Research, 2023)
This study aims to find out the extent to which Indomie products (brands) can influence consumer interest in Indomie products. Brand equity keeps customers loyal to products of any type and price. Currently, the selection criteria are at the technical level of the brand. The three basic components are: consumer perception, negative or positive effects, and the resulting value. Quantitative methods were used in the study. Data collection was carried out using questionnaires. The respondents of this study were buyers of Indomie products. Then the number of samples taken amounted to 150 respondents spread throughout Indonesia. The analysis technique used is SEM analysis and is processed with the AMOS application. The results showed that brand image has a positive and significant effect on brand awareness, brand awareness and brand image have a positive and significant effect on brand loyalty, and brand awareness and brand loyalty have a positive and significant effect on brand equity.